Indigenous sheep resources of Ethiopia: Types, production systems and farmers preferences - Gizaw, Solomon; Komen, Hans; Hanotte, Olivier H.; Arendonk, Johan A.M. van (Cambridge University Press, 2008)
Ethiopia has a diverse sheep population, numbering 23.6 million, in parallel with its diverse ecology, production systems and communities. A comprehensive phenotypic and genetic characterization of Ethiopian sheep populations was initiated in 2005 to provide a nationwide framework for the management of sheep genetic resources. In this paper, we describe the indigenous sheep types in terms of physical characteristics, eco-regional distribution and community affinity. We also present relationships of sheep types with agricultural production systems, and farmers'/pastoralists' assessment of their sheep types. Fourteen traditionally recognized sheep types were identified and physically described.The sheep types could be categorized into four groups (sub-alpine short-fat-tailed, highland long-fat-tailed, lowland fat-rumped and lowland thin-tailed) based on their ecological distribution, tail types (fat-tail versus thin-tail), tail form/shape, and fiber type. There is high morphological and ecological diversity among the major sheep groups as well as among the sheep types. There is also a strong relationship between sheep types, ethnic groups and production systems. Assessment of the genetic distinctiveness of the traditional sheep types is important for developing rational conservation-based improvement programs. Molecular genetic assessment of the population structure is a follow up activity.